Risk analysis of a hedge fund oriented on sustainable and responsible investments for emerging markets - Gabriela Prelipcean; Mircea Boscoianu (Amfiteatru Economic Journal, 2020)
The aim of this paper is to analyse the development strategies of an innovative Special Purpose Vehicle (SPV) for sustainable and responsible investments (SRI). This contribution represents a premiere for the Romanian capital market, an emerging market with low liquidity and limited diversification possibilities through alternative investments, because it highlights both the integration of specific tools for sustainable development and the possibility of obtaining good performance (risk-return) through the link of alternative instruments and strategies. Starting from the analysis of sustainable and responsible investment possibilities (SRI), it is justified the feasibility of integrating an active investment strategy, by using an innovative Hedge Fund architecture oriented towards sustainable and responsible investments (called HF-SRI). In this case, a natural and flexible integration of the sustainability principles in emerging capital markets can be achieved. In addition, the possibility of applying the satellite sub-portfolios method in the global analysis of the performance management combined with the risk analysis is justified. The case study presents an intuitive, simple, but effective model based on applying the Analytical Hierarchy Process (AHP) to the eight risks identified by experts, grouped into three categories and associated with a HF-SRI architecture type with two basic sub-portfolios, oriented on innovative alternative instruments: venture capital funds (VCFs) and exchange traded funds (ETFs).
Keywords: Q01; Q16; M14; G32; G24; 330; economic-social-governance (ESG) factors; hedge fund for sustainable and responsible investments (HF-SRI); venture capital funds (VCF); exchange-traded funds (ETFs); Analytical Hierarchy Process (AHP)